2020
DOI: 10.1186/s13071-020-04150-x
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase (ace-1R) target site mutation G119S and resistance to carbamates in Anopheles gambiae (sensu lato) populations from Mali

Abstract: Background: The long-lasting insecticidal nets (LLINs) and indoor residual spraying of insecticide (IRS) are major malaria vector control strategies in Mali. The success of control strategies depends on a better understanding of the status of malaria vectors with respect to the insecticides used. In this study we evaluate the level of resistance of Anopheles gambiae (sensu lato) to bendiocarb and the molecular mechanism that underlies it. Methods: Larvae of An. gambiae (s.l.) were collected from breeding habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
2
8
1
Order By: Relevance
“…gambiae ( s.s. ), respectively ( Grau-Bové et al., 2021 ). Unlike some previous studies in Côte d’Ivoire where the resistant alleles were found only in heterozygous form ( Edi et al., 2012 ; Assogba et al., 2016 ; Keïta et al., 2020 ), our study revealed the presence of homozygous resistant genotypes in both An. coluzzii and An.…”
Section: Discussioncontrasting
confidence: 99%
“…gambiae ( s.s. ), respectively ( Grau-Bové et al., 2021 ). Unlike some previous studies in Côte d’Ivoire where the resistant alleles were found only in heterozygous form ( Edi et al., 2012 ; Assogba et al., 2016 ; Keïta et al., 2020 ), our study revealed the presence of homozygous resistant genotypes in both An. coluzzii and An.…”
Section: Discussioncontrasting
confidence: 99%
“…This absence of bendiocarb resistance was associated with a slow decrease of the G119S ace1 mutation commonly associated to carbamate and organophosphate resistance in An. gambiae (16,25,(70)(71)(72). This trend might be explained by the low initial frequency of the ace1 mutation in the parental line and its signi cant genetic cost (16, 73), or by the lower selection pressure exerted by carbamates and organophosphates present in the agrochemical mixtures as compared to other compounds such as pyrethroids and organochlorines.…”
Section: Larval Selection With Agrochemical Mixtures Select For Incre...mentioning
confidence: 99%
“…Phenotypic resistance was also observed with carbamates to the three species, which was consistent with acetylcholinesterase (ace-1 R ) target-site mutation in all vector species studied. 31 The three species of A. gambiae s.l. were fully susceptible to the organophosphates (pirimiphos-methyl) at each study site.…”
Section: Wa-icemr Entomological Studies and The Potential Value Of Ve...mentioning
confidence: 99%